Análise do comportamento em serviço de pilares esbeltos de concreto armado - Joao Augusto Lobo Pereira (2006)
This work presents a mathematical formulation able to describe, in a more efficient way than the conventional methods, the behavior in service of slender reinforced concrete columns of any geometric section submitted to normal flexural forces. An analysis of the columns behavior in service is developed to determine the long-term deformations that occur at each concrete element that form the several transversalsections of the column. For this, the creep is considered as a linear phenomenon. Only isostatic columns are considered. Graphics with results of two columns using the proposed method are presented. One of the graphics was made for the slenderness ratio of ë = 90, the other for ë = 140. The column in the ultimate limit state will be analyzed in a posterior study, in which the hyperestatic columns submitted to normal flexural forces will be also analyzed.